Ciliwung River Pollution Case Study: Analysis of Causal Factors and Impact Reduction Regulations - Agatha, Claudia; Sherlyn, Sherlyn; Setiawati, Shelly Adisti; Sinaga, Maria Adelweys Niken Aprilia; Andreyn, Sheilla Virginia; Santoso, Agnellya Hendarmin; Kanaishia, Indy; Adhinugraha, Ahmad Shiddiq (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The environment is a very important aspect of human life, which functions as the main source for fulfilling various needs. The environmental problems that occur frequently and are commonly encountered today are water pollution. One of the water sources that is currently very polluted is rivers. This study aims to analyze the factors and impacts of the pollution in the Ciliwung River, and determine the regulations that have been implemented to reduce this pollution. The research method used in writing this paper is the normative legal research method. In this study, the authors used primary legal materials and secondary legal materials. Primary legal materials, namely statutory regulations and official documents containing legal provisions, while secondary legal materials are materials that provide explanations related to primary legal materials. The results obtained in this study indicate that a few factors causing pollution of the river is the lack of awareness of local residents who still throw garbage into the river, as it has an impact on the water quality, public health, damage to the ecosystem around the river and impact on social and economic losses. The regulations that have been issued and implemented by the government to reduce pollution in the Ciliwung River, one of which is the Undang-Undang (UU) Nomor 18 Tahun 2008 tentang Pengelolaan Sampah regulating the waste management in Indonesia. So, the water pollution that occurs cannot be separated from irresponsible human actions or activities and to deal with this, the role of the government is needed to increase public awareness in dealing with this pollution.